Beans, Peas, and Lentils: Health Benefits - Lakshmi Mahan; Lauren Foster; Wendy Dahl (EDIS)
Bean, peas, and lentils are known collectively as legumes or pulses. Beans are great sources of many nutrients, including protein, fiber, and potassium. They can be placed either in the vegetable group or the protein group of MyPlate. If you have consumed enough protein choices, then you can count them in the vegetable group, and vice versa. This 2-page fact sheet was written by Lakshmi Mahan, Lauren Foster, and Wendy J. Dahl, and published by the UF Department of Food Science and Human Nutrition, May 2013.